With the best will in the world: How benevolent sexism shapes medical careers. Issue 2 (22nd January 2020) - Stone, Louise; Phillips, Christine; Douglas, Kirsty A.
Abstract : A compliment is not a compliment when it stereotypes, undermining self‐efficacy and performance. To overcome "benevolent sexism" we must recognise and act on unconscious behaviour such as complimenting women's relational skills over their agency and competence.